Cost-effectiveness of monitoring free flaps. Issue 5 (June 2016) - Subramaniam, Shiva; Sharp, David; Jardim, Christopher; Batstone, Martin D.
Abstract: Methods of free flap monitoring have become more sophisticated and expensive. This study aims to determine the cost of free flap monitoring and examine its cost effectiveness. We examined a group of patients who had had free flaps to the head and neck over a two-year period, and combined these results with costs obtained from business managers and staff. There were 132 free flaps with a success rate of 99%. The cost of monitoring was Aus 193/flap. Clinical monitoring during this time period cost Aus25 476 and did not lead to the salvage of any free flaps. Cost equivalence is reached between monitoring and not monitoring only at a failure rate of 15.8%. This is to our knowledge the first study to calculate the cost of clinical monitoring of free flaps, and to examine its cost-effectiveness.